Proton tunnelling in ribosomal peptide bond formation / Hadieh Monajemi - Hadieh , Monajemi (2018)
Proton transfer reactions are simple yet important reactions which have been immensely investigated in different studies due to their dominance in many chemical and biochemical systems. The dual wave-particle nature of protons enables them to tunnel through classically high potential energy barriers. Being temperature independent, proton tunnelling can occur at any temperature. Hence, many studies have suggested that some enzymatic reactions with high energy barriers go through proton tunnelling. However, the occurrence of tunnelling has not yet been investigated in one of the most puzzling enzymatic reactions, i.e. the process of peptide bond formation in a large complex enzyme called the ribosome. A large part of this study aims to investigate the tunnelling behaviour in this mechanism using computational quantum chemistry tools and theoretical methods. We proposed three novel proton transfer mechanisms for this reaction which are based on three different crystallographic structures. Using density functional theory, we first obtained the structural and physical information about these reaction mechanisms. The rate of these reactions were then calculated using reaction rate theories with classical motion approximation. Ultimately, the tunnelling correction was calculated numerically and added to the classical reaction rate to investigate the tunnelling behaviour of proton. The results show that in one of our novel proposed mechanisms, the ribosome induces tunnelling by thinning the energy barrier width through shortening the proton donor-acceptor distance. This explains the unexpectedly high rate of ribosomal peptide bond formation. Using this idea, we attempted to induce tunnelling in a synthetic reaction and increase its efficiency. For this purpose, we studied the reaction of boronic acid with diols which is important in designing an efficient non-enzymatic glucose sensor for blood glucose monitoring applications. The results indicate that one way to induce tunnelling through decreasing the donor-acceptor distance is to increase the electronegativity of the R-group. The transition structure for the highest electronegative R-group exhibits the shortest proton path from boronic acid to diol. The direct correlation of the electronegativity and the tunnelling corrected reaction rate further supports the importance of the lower donor-acceptor distance in inducing tunnelling.